Answer:
x = 7, y = 10.5.
Explanation:
y = 2x - 3.5
-2y = -x - 14
Multiply the first equation by 2:
2y = 4x - 7
Now add this equation to the second one:
0 = 3x - 21
3x = 21
x = 7.
Now substitute x = 7 in the first equation to fund the value of y:
y = 2(7) - 3.5
y = 10.5.
x=7
y=10.5
1. You can apply the method of substitution, as you can see below:
- Substitute into the other equation and solve fo x:
- Substitute the value of x obtain into the first equation, then the value of y is:
5.2m questions
6.7m answers